Seed germination studies of tree species: Radermarchera xylocarpa and Dolicandrone falcata - Trivedi, DR; Joshi, AG; Nagar, PS (Bangladesh Journal of Scientific and Industrial Research, 2016)
Seeds of Radermarchera xylocarpa and Dolicandrone falcata were soaked overnight in water and germinated in different substrates. In both the plants, the highest percent of germination was recorded in cocopeat (Radermarchera xylocarpa:62%; Dolicandrone. falcata: 41%) followed by MS basal medium (Radermarchera xylocarpa: 46%; Dolicandrone falcata:20%), cocopeat: sand (Radermarchera xylocarpa:30%; Dolicandrone. falcata: 8%) and least being in filter paper (Radermarchera xylocarpa: 23%; Dolicandrone falcata: 0%). Prior to germination in optimised substrate, seeds were soaked overnight in distilled water (control) and in gibberllic acid (GA3) (5 & 10 ?M). In both the plants GA3 treated seeds failed to increase percent germination and the growth of seedlings. In control the seedling growth was better with respect to all the parameter for both the species. Seedlings which were grown in cocopeat, rapidly developed into healthy plants after transfer to field Bangladesh J. Sci. Ind. Res. 51(1), 41-46, 2016